2002
DOI: 10.1103/physrevlett.88.051802
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Photon Polarization inBKππγ

Abstract: We propose a way of measuring the photon polarization in radiative B decays into K resonance states decaying to Kππ, which can test the Standard Model and probe new physics. The photon polarization is shown to be measured by the up-down asymmetry of the photon direction relative to the Kππ decay plane in the K resonance rest frame. The integrated asymmetry in K1(1400) → Kππ, calculated to be 0.34 ± 0.05 in the Standard Model, is measurable at currently operating B factories.The Standard Model (SM) predicts tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
143
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 27 publications
1
143
0
Order By: Relevance
“…[17,18] and improved in [19]. Our study shows that the photon polarization parameter λ γ can be measured at super B factories with an accuracy ∼ 20%, with integrated luminosity of 75 ab −1 .…”
Section: Jhep08(2012)090 6 Conclusionmentioning
confidence: 82%
See 2 more Smart Citations
“…[17,18] and improved in [19]. Our study shows that the photon polarization parameter λ γ can be measured at super B factories with an accuracy ∼ 20%, with integrated luminosity of 75 ab −1 .…”
Section: Jhep08(2012)090 6 Conclusionmentioning
confidence: 82%
“…For example, p γ · ( p π × p K ) is a pseudo-scalar; then applying the parity transformation it will have the different sign for left-and right-handed photons. Gronau et al [17,18] proposed to study the angular distribution in the B → K 1 (→ Kππ)γ decay and extract the polarization parameter λ γ ,…”
Section: Ggpr and Ddlr-inspired Methods Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to K * , higher resonances of Kaon also deserve much attention. Especially, it was suggested that B → K res (→ Kππ)γ can provide a direct measurement of the photon polarization [15]. In particular, it was shown that B → K 1 (1400)γ can produce large polarization asymmetry of ≈ 33% in the standard model.…”
Section: Introductionmentioning
confidence: 99%
“…[4]. Exclusive decays, such as B → K 1 (1400)γ, can also be used to measure the photon helicity, which may differ from the SM prediction in some new physics models [5].…”
Section: Introductionmentioning
confidence: 99%